Humanism and the Bible in the poetry of Benito Arias Montano (ca. 1525-1598) - Czepiel, M (2022)
Benito Arias Montano (ca. 1525–1598) is known for his polymathic scholarly interests. However, for him, humanist learning had to be put to the service of the study of the Bible. While the erudition of Arias Montano’s prose treatises has seen an increase in critical attention in recent years, his poetry is still understudied. This thesis shows that the fruits of his learning can also be seen in his original lyric poetry. However, I argue throughout this study that Arias Montano’s poetry betrays an anxiety about the limitations and proper use of humanist scholarship.